A Patient-Derived Screen Identifies HDAC Inhibitors as Enhancers of Phagocytosis and Potent Immunotherapy Partners - Mona Khalaj; Andrew T. Burden; Madison L. Gutierrez; Sophia C. Hoonsbeen; Parisa Nejad; Tal Raveh; Jacob S. Young; Faranak Fattahi; Irving L. Weissman (Cancer Immunology Research, 2026)
Abstract Glioblastoma multiforme (GBM) is a lethal brain tumor with limited treatment options. Tumor-associated macrophages and microglia (TAM) drive immune suppression and tumor progression, making them a key therapeutic target for GBM. Enhancing TAM phagocytosis in GBM has shown promise, particularly with innate checkpoint inhibitors, such as CD47-blocking antibodies. However, small-molecule approaches, which offer tunable and potentially synergistic mechanisms, remain underexplored in this context. In this study, we conducted a large-scale small-molecule screen on primary TAMs isolated directly from tumors of patients with GBM, testing 1,365 compounds to identify drugs that enhance TAM phagocytosis. This screen revealed enrichment for histone deacetylase (HDAC)-targeting drugs among the top hits. HDAC inhibitors enhanced phagocytosis of cancer cells across multiple primary human TAM–GBM combinations and synergized with CD47 blockade ex vivo. In a xenograft GBM model, pracinostat suppressed tumor growth and extended survival, with additive benefit when combined with CD47 antibodies. RNA sequencing and H3K27Ac cleavage under targets and tagmentation profiling of pracinostat-treated TAMs in vivo revealed a two-tier mechanism: transcriptional reprogramming toward a proinflammatory state via NF-κB activation and epigenetic priming of FcγR-mediated phagocytic machinery, providing a mechanistic basis for the observed synergy with CD47 blockade. Our findings establish a patient-first functional screening platform for identifying TAM reprogramming therapeutics in GBM, validate HDAC inhibitors as a lead class that potentiates innate checkpoint immunotherapy, and provide additional candidate compounds for clinical investigation.